Prediction of In-Hospital Mortality in Spontaneous Bacterial Peritonitis Patients with Advanced Liver Disease - Adil Hassan, Rehmatullah Bhatti, Abdul Hafeez, Jawed Iqbal, Laraib Jamali, Sajan Sawai, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Bacterial infections are known reason for morbidity and mortality in hospitalized patients with cirrhosis among which Spontaneous bacterial peritonitis (SBP) is most common, accounts for around 20% to 30% mortality rate. Objective: To evaluate the frequency of in-hospital mortality in SBP patients. Study Design: Descriptive case series. Setting: Asian Institute of Medical Sciences Hospital Hyderabad. Duration: From 1st January 2019 to 30th June 2019. Material and Methods: Adult patients diagnosed to have spontaneous bacterial peritonitis and followed for outcome. Results: 223 patients of spontaneous bacterial peritonitis I,e 165 (74%) male and 58 (26%) female fulfilling the inclusion criteria were enrolled in study. Mean age obtained was 47.56 ± 13.069 years and Hepatitis C with most common etiology for CLD was 128 (57.4%) followed by Hepatitis B 26 (11.7%), Hepatitis B + D 30 (13.5 %) and Alcohol 8 (3.6 %). Hepatocellular carcinoma in 70 (31.4 %) only. CTP (Child-Turcot-Pugh) score and MELD (Model for End-stage Liver Disease) score used to access stage of cirrhosis. 38 (17 %) patients with CTP class B and 185 (83 %) with CTP class C. The mean MELD score of all patients found to be 23.09 ± 15.686. Among 223 patients, in-hospital mortality was observed in 61 (27.4%), 115 (51.6%) were discharged with improvement and rest 47 (21.1%) discharged with no improvement. Practical Implication: This study's findings underscore the need for early detection and aggressive management of Spontaneous Bacterial Peritonitis in patients with advanced liver disease, especially those with CTP Class C and high MELD scores, to reduce the high in-hospital mortality rate. Conclusion: Significantly high in-hospital mortality was found to be associated with SBP, with CTP Class C, High MELD Score, increased creatinine, bilirubin, PT, INR and decreased albumin especially in females. Keywords: Cirrhosis; In-hospital mortality; Spontaneous bacterial peritonitis